The Factors Affecting the Composite Stock Price Index (CSPI) of Indonesia Stock Exchange - Prawoto, Nano; Putra, Bagus Ardyan (Jurnal Ekonomi & Studi Pembangunan, 2020)
The study examines the influence of The Fed Rate, inflation, Dow Jones Index (DJI), exchange rate, and world oil price on the composite stock price index (CSPI) in Indonesia. The method used in this study was the Vector Error Correction Model (VECM). The research showed that the influence of inflation towards the composite stock price index was negative both in the short term and long term. The influence of the exchange rate towards the composite stock price index was positive both short term and long term. The impact of oil price towards composite stock price index was positive in the short term and long term. However, both the Dow Jones Index (DJI) and The Fed Rate had a negative effect on the composite stock price index. The results of this analysis can be used as a reference for investor and government policymaking